2016
DOI: 10.1111/dme.13166
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the independent effect of HbA1c variability on adverse health outcomes in patients with Type 2 diabetes

Abstract: In veterans with Type 2 diabetes, greater HbA variability was associated with an increased risk of adverse long-term outcomes, independently of HbA levels and direction of change. Limiting HbA fluctuations over time may reduce complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 28 publications
2
47
0
1
Order By: Relevance
“…Previous studies have shown increased mortality in people with Type 2 diabetes who have higher HbA 1c variability . Although it is known that HbA 1c variability increases microvascular complications in Type 1 diabetes there is no previous evidence of increased mortality in this group .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies have shown increased mortality in people with Type 2 diabetes who have higher HbA 1c variability . Although it is known that HbA 1c variability increases microvascular complications in Type 1 diabetes there is no previous evidence of increased mortality in this group .…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have shown increased mortality in people with Type 2 diabetes who have higher HbA 1c variability [4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 95%
“…9 In a Japanese observational cohort study, Bouchi et al 16 observed an increased incidence of CVD in patients with higher variation in HbA1c-SD. Recently, Prentice et al 17 carried out a retrospective cohort study in veterans with type 2 diabetes and concluded that all HbA1c variability measures significantly predicted adverse outcomes. In the present study, we also found that higher HbA1c variability was associated with the presence of atherosclerosis/ CVD.…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognised that chronic hyperglycaemia, as measured by HbA1c, is the key risk factor for the development of diabetes-related micro and macrovascular complications [7,8]. Several recent studies have suggested that there are relationships between the development of micro and macrovascular complications and the variation between HbA1c values at successive clinic visits [9,10,11,12,13,14]. These changes have been termed glycaemic variability.…”
Section: Introductionmentioning
confidence: 99%